Penguatan Keaswajaan bagi Generasi Muda di Era Digital melalui Workshop Content Writer Berbasis Aswaja - Ulumuddin, Imam Khoirul; Shobirin, Ma'as; Prasetyo, Areif; Mufidah, Luluk Nur (Kifah: Jurnal Pengabdian Masyarakat, 2024)
Digitalization provides challenges and opportunities in the spread of Islamic literacy. As an Islamic-based university, Wahid Hasyim University through the Aswaja Study Center carries out Community Service through content writer training for students who want to develop Aswaja value-based writing skills. This training is important, considering the high internet penetration in Indonesia and the low quality digital literacy among the younger generation. This service program uses the Participatory Learning and Action (PLA) method or participatory learning and practice. The material presented was in the form of Islam, creative content, the use of social media and several other relevant materials. The service program through this training aims to improve students' ability to write content based on Ahlussunnah wal Jama'ah (Aswaja) values, as part of efforts to develop digital skills in the modern era. This program not only focuses on technical writing skills, but also on the underlying Islamic values, such as honesty, integrity, and justice and also produces students who are able to deliver educational and inspirational content in the digital space. The design of the activity is in the form of training aimed at Wahid Hasyim University students, especially Young Aswaja Activists (PAM). The result of this activity is that the participants are able to write good content based on Aswaja through the assignment of making an article which will later be published on the Aswaja Muda Unwahas website after going through a selection from a team of experts.